Storage Area Networks (SANs) in Business Environment - Mat Rejab, Mohd Razif (Universiti Teknologi Petronas, 2004)
Storage Area Networks (SAN) in Business Environment is titled and initiated to design and implement Storage Area Networks architecture in the business operation. The project is divided into two terms, first is the research ofStorage Area Networks and the second is system development onthe Storage Area Networks Knowledge Management System. Research on the Storage Area Networks was based on the problem statement and objective of the project while the Storage Area Networks Knowledge Management System is the system in making decision to implement Storage Area Networks. The project will require a hybrid model for System Development Life Cycle (SDLC) methodology. Reviews on the system will be made according to the SDLC and the objectives of the project. Artificial Intelligent module is used for the Storage Area Networks system to determine the best Storage Area Networks solution for the business. Research will be more onthe implementation of the Storage Area Networks in the business based onthe cost, availability and the architecture of the Storage Area Networks. Advantages of the Storage Area Networks and several criteria inthe Storage Area Networks will be part of the Storage Area Networks research. Storage Area Networks give the best solution for business as the database is an important asset for the business. Performance, availability, flexibility and scalability are the main subject in considering Storage Area Networks. Keywords: Storage Area Networks, Knowledge Management System, hybrid model. System Development Life Cycle